Prevalence and related factors of healthy aging: A systematic review and meta-analysis - Tang, Linxi; Binti Rasudin, Nur Syahmina; Dong, Yuan; Yusuf, Azlina (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Healthy aging is a key goal of global public health and aging policy initiatives. Understanding its prevalence and associated determinants is essential for designing targeted interventions and promoting well-being among older adults. Objective: This study aimed to estimate the global prevalence of healthy aging and to identify its associated factors across different countries. Methods: A systematic review and meta-analysis were conducted. A comprehensive literature search was conducted in Web of Science, PubMed, EBSCO Discovery Service (EDS), Scopus, and ProQuest from database inception to February 2025. Two independent reviewers screened articles, extracted data, and assessed study quality using the Newcastle-Ottawa Quality Assessment Scale (NOS) and the Agency for Healthcare Research and Quality (AHRQ) Methodology Checklist. Eligible studies were included in a meta-analysis using Stata 18.0 and R version 4.5.0. Results: A total of 39 studies involving 300,624 participants were included. The pooled prevalence of healthy aging was 23.0% (95% CI: 18%–27%). After adjusting for publication bias using the trim-and-fill method, the estimate decreased to 15.6% (95% CI: 11.0%–20.1%), suggesting possible overestimation in the original estimate. Significant associations with healthy aging were found for age (≥75 years), gender, marital status, educational level, economic level, social participation, employment status, economy, smoking status, alcohol consumption, physical activity, body mass index (BMI), and self-rated health. Conclusions: The findings indicate that fewer than one in four older adults meet the criteria for healthy aging globally, with substantial variation across regions. A wide range of sociodemographic, behavioral, and health-related factors influence this outcome. These results underscore the importance of addressing modifiable determinants in future public health efforts to promote healthy aging. Registry: PROSPERO [CRD42024542942]